Development of creativity: design and evaluation of a program of intervention - Allueva, Pedro (2002)
The intervention program based on the five stages of the Amabile´s creative process was applied to a group of second year students majoring in industrial design considering the combination of intellectual attributes, cognitive style, personality and strategies. There was an effort to eliminate barriers to creativity, creating a suitable atmosphere that encouraged adequate attitudes to develop creative skills. Results show that creative programs in schools, adapted to students’ characteristics, will promote an increase in creative skills.